Markers of tumor inflammation as prognostic factors for overall survival in patients with advanced pancreatic cancer receiving first-line FOLFIRINOX chemotherapy. (4th May 2022) - Kamposioras, Konstantinos; Papaxoinis, George; Dawood, Mohamed; Appleyard, Jordan; Collinson, Fiona; Lamarca, Angela; Ahmad, Usman; Hubner, Richard A.; Wright, Francesca; Pihlak, Rille; Damyanova, Iva; Razzaq, Bilal; et al.
Abstract: Background: Identifying pretreatment blood markers that distinguish prognostic groups of patients with advanced pancreatic ductal adenocarcinoma (PDAC) under first-line FOLFIRINOX chemotherapy has the potential to improve management of this condition. Aim of this study was to determine the prognostic utility of a range of pretreatment, inflammation-related, blood cell markers in this group of patients. Material and methods: Data from a training cohort were analyzed to identify potential pretreatment blood markers correlating to survival outcomes. The most informative markers were further analyzed in a validation cohort comprised patients from a geographically separate cancer center undergoing the same treatment. Results: A total of 138 consecutive patients receiving FOLFIRINOX chemotherapy between 2010 and 2019, constituted the training cohort. Neutrophil/lymphocyte (NLR), monocyte/lymphocyte (MLR), and platelet/lymphocyte ratio (PLR) as well as the systemic inflammatory response index (SIRI) and CA19.9 showed prognostic significance in addition to tumor stage. A pretreatment SIRI score cutoff of 2.35 differentiated between a poor prognostic group with median overall survival (mOS) 5.1 months and a better prognostic group, mOS 12.5 months. SIRI ≤/> 2.35 was predictive of mOS in patients with locally advanced and metastatic PDAC. SIRI was confirmed as a prognostic marker in a validation cohort of 67 patients with mOS of 13.4 months and 6.3 months for those with SIRI ≤ 2.35 and >2.35, respectively. Additional analysis revealed baseline SIRI as being prognostic within additional subgroups of patients in both cohorts. Conclusions: This large, retrospective, analysis of real-world patients receiving first-line FOLFIRINOX chemotherapy for advanced PDAC has identified the pretreatment blood SIRI as a strong prognostic marker for survival. This will allow better counseling of patients with regards to the benefits of treatment, improved stratification within clinical trials, and potentially identify groups of patients for novel therapy trials as first-line treatment.